2008
DOI: 10.1002/pds.1656
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term use of antihypertensive drugs and risk of cancer

Abstract: The long-term use of commonly prescribed classes of antihypertensive drugs does not appear to promote or initiate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 40 publications
2
71
0
1
Order By: Relevance
“…4,15,16,[29][30][31]35 All but 2 of the 16 case-control studies reported the number of cases (n = 27 987) and controls (n = 119 879). 5,6,[9][10][11][12][13]18,19,21,[23][24][25]28 The proportion of participants who used an ACE inhibitor or angiotensin-receptor blocker was 7.3% among the cases and 7.9% among the controls. Tables 1 and 2 show the general characteristics of the studies included in the analyses.…”
Section: Articles Screened N = 3735mentioning
confidence: 99%
See 3 more Smart Citations
“…4,15,16,[29][30][31]35 All but 2 of the 16 case-control studies reported the number of cases (n = 27 987) and controls (n = 119 879). 5,6,[9][10][11][12][13]18,19,21,[23][24][25]28 The proportion of participants who used an ACE inhibitor or angiotensin-receptor blocker was 7.3% among the cases and 7.9% among the controls. Tables 1 and 2 show the general characteristics of the studies included in the analyses.…”
Section: Articles Screened N = 3735mentioning
confidence: 99%
“…A beneficial effect was also found when the analysis was limited to the 11 studies with long-term follow-up (RR 0.89, 95% CI 0.83-0.96). 4,6,13,15,18,[22][23][24]27,31,33 When the analyses were restricted to studies that investigated the effect of only ACE inhibitors on cancer risk, the 12 cohort and nested case-control studies showed a nonsignificant protective effect (RR 0.93, 95% CI 0.86-1.01), 4,12,15,16,19,21,23,29−33 and the 8 studies with longterm follow-up showed a significant protective effect (RR 0.89, 95% CI 0.80-0.98). 4,13,15,18,22,23,31,33 No significant change was observed when we excluded two studies with crude estimates.…”
Section: Effect Of Medication Use On Risk Of Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The results are equivocal with a number of studies demonstrating an increased risk of cancer after HTDT and others finding either no effect or a protective effect (1)(2)(3)(4)(5)(6)(7). Angiogenesis may be a factor underlying the relationship between cancer and HTDT.…”
Section: Introductionmentioning
confidence: 95%